Philosophy Study in the Development of Reading Teaching Materials Based on Cultural Wisdom of Betawi Fairy Tales - Danti Pudjiati; Venti Mawarni (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
The purpose of this study was to examine the philosophical study contained in the development of reading teaching materials based on cultural wisdom of Betawi fairy tales for grade X science students at SMAN 107 Jakarta. This research wasÂ  qualitative research with a descriptive method. Data collection techniques were carried out through library research on references related to the topics discussed namely teaching materials, readings, and Betawi fairy tales. The results of this research regarding the development of reading teaching materials based on cultural wisdom of Betawi fairy tales then were analyzed using three philosophical studies namely Ontology, Epistemology and Axiology. The Ontology study was employed to examine the development of reading teaching materials with cultural wisdom of Betawi tales. Next, Epistemology was formulated to design and make prototypes of the development of teaching materials so that they can be evaluated and get feedback from the parties involved. Subsequently, the axiology which focused on value of educational technology was intended to intrigue and promote a sense of humanity among students through the depiction of the characters told in the fairy tale.